KELAYAKAN FLIPBOOK SUB MATERI TUMBUHAN PAKU (Pteridophyta) DI KELAS X SMA - Eka Aprilia; Syamswisna Syamswisna; Titin Titin (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractThis study aims to determine the feasibility of the flipbook in sub material offerns (Pteridophyta). The form of the study was qualitative with descriptivemethod. Flipbook media was made based on data of ferns in Mempawah Huluand use glossy double sided paper with size 21 cm x 28 cm as materials. Theshape of flipbook media was made like a calendar or photo album. The flipbookmedia which have been made was validated using a flipbook media validationquestionnaire with a Likert scale by five validators (two lecturer of BiologyEducation FKIP UNTAN and three teachers of biology on Class X Highschool). Then, it was analyzed based on the Content Validity Ratio (CVR) andContent Validity Index (CVI) approach by Lawshe (1975). The validationresults from the flipbook media stated that the flipbook was valid with a CVRvalue of 1.00 or exceeding 0.99 in each criterion, same as CVI score. It can beconcluded that the flipbook of fern sub material is valid to be used as a learningmedia in Class X High School.Keywords: Feasibility, Ferns, Flipbook,